2010
DOI: 10.1177/0097700409360745
|View full text |Cite
|
Sign up to set email alerts
|

Informal Lenders and Rural Finance in China: A Report from the Field

Abstract: Chinese farmers need loans. It’s hard for them to borrow from formal lenders like banks or even the rural credit cooperatives. Thus, to satisfy their financial needs, farmers borrow from informal lenders. While farmers have benefited from the post-Mao reform in many respects, financial reforms of the past three decades have failed to create an effective system in which farmers can borrow from formal lenders. To create an effective and efficient financial system that can meet farmers’ needs, it is necessary for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 22 publications
(19 reference statements)
0
10
0
Order By: Relevance
“…For one, there can be no doubt that the rural financial system -and especially credit provision -has played a critical role in the transformative and unprecedented development of rural China since the reform and opening. In particular, rural development has depended on the financing of agricultural producers and township and village enterprises (TVEs), as well as the transfer of remittances from migrant workers in urban areas back to their rural origins (Cheng, 2006;Tsai, 2002;Zhou & Takeuchi, 2010), making it important to examine how different financial institutions and services have facilitated different types of development for different areas and actors. At the same time, there are innumerable examples, in different contexts and throughout history, of financial systems and institutions causing severe crises, often with catastrophic outcomes for local, regional, and national economies.…”
Section: Research Questions and Objectivesmentioning
confidence: 99%
“…For one, there can be no doubt that the rural financial system -and especially credit provision -has played a critical role in the transformative and unprecedented development of rural China since the reform and opening. In particular, rural development has depended on the financing of agricultural producers and township and village enterprises (TVEs), as well as the transfer of remittances from migrant workers in urban areas back to their rural origins (Cheng, 2006;Tsai, 2002;Zhou & Takeuchi, 2010), making it important to examine how different financial institutions and services have facilitated different types of development for different areas and actors. At the same time, there are innumerable examples, in different contexts and throughout history, of financial systems and institutions causing severe crises, often with catastrophic outcomes for local, regional, and national economies.…”
Section: Research Questions and Objectivesmentioning
confidence: 99%
“…Du, 2004;Feder et al, 1989;Feng et al, 2006;He, 2008;He et al, 2009;OECD, 2003). At the same time, however, some researchers argue that credit constraints are not universally or evenly observed in the rural Chinese context, pointing to data that show widespread and sometimes concurrent use of both formal and informal sources (Park & Ren, 2001;Tsai, 2004;Zhou & Takeuchi, 2010). Other studies contest the predominant view that low-income rural households have high demand for loans by showing that many such households have actually decided not to participate in credit programmes based on careful calculations of potential risks and returns (Bislev, 2010(Bislev, , 2012Park & Ren, 2001;Turvey & Kong, 2010).…”
Section: Supply Demand and Impact Assessmentmentioning
confidence: 99%
“…These investigations have found that loans are often used for 'productive' purposes -such as investment in agriculture, TVEs, microenterprises, and to facilitate rural-urban migration. At the same time, loans are also frequently used for 'non-productive' purposes -such as children's education, healthcare, house construction, consumer durables, weddings, funerals, and daily necessities -which is generally conceptualised as 'consumption smoothing' (Park, Ren, & Wang, 2003;Unger, 2002b;Zhou & Takeuchi, 2010). These studies usually come to the conclusion that easier access to credit -i.e.…”
Section: Supply Demand and Impact Assessmentmentioning
confidence: 99%
“…Farmers are particularly affected by the situation, with many being forced to use other more informal channels to get loans (Zhou & Takeuchi, 2010). The main reason behind this is that they lack eligible collateral, as they do not own their land and cannot use it to insure banks against future liquidity shortfalls.…”
mentioning
confidence: 99%